2017
DOI: 10.1080/14786419.2017.1416375
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis of non-polar solvent extracts of theWisteria sinensisleaves

Abstract: A comparative study on the phytochemical composition of the n-hexane and chloroform extracts from Wisteria sinensis leaves collected in June and October is described. Continuous extraction in Soxhlet apparatus, as well as ultrasound-assisted technique, was used for the preparation of the extracts. All the extracts were analysed by GC/MS method. As a result, α-tocopherol was identified as the main component (56%) of the extracts from October leaves, whereas, β-sitosterol was identified as the main compound (47%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Phenolic acids, flavonoids, tannins, alkaloids, etc., can be extracted in polar or less polar solvents [ 19 ]. In comparison, components of essential oils and tocopherol can be obtained through extraction in nonpolar solvents [ 20 ]. Thus, solvent-based plant extracts can help us to reach the specific group of plant compounds that is responsible for the synthesis of nanoparticles with high bactericidal activity, stability, and dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, flavonoids, tannins, alkaloids, etc., can be extracted in polar or less polar solvents [ 19 ]. In comparison, components of essential oils and tocopherol can be obtained through extraction in nonpolar solvents [ 20 ]. Thus, solvent-based plant extracts can help us to reach the specific group of plant compounds that is responsible for the synthesis of nanoparticles with high bactericidal activity, stability, and dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, flavonoids, tannins, and alkaloids etc., can be extracted in polar or less polar solvents (10). In comparison, components of essential oils and tocopherol can be obtained through extraction in nonpolar solvents (11). Thus, solvent based plant extracts can help us to reach the specific group of plant compounds that is responsible for the synthesis of nanoparticles with high bactericidal activity, stability, and dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Cogn, Luffa cylindrica (L.) Roem, and Cucurbita pepo L. have been consumed in China for decades, and are commonly considered to be vegetables. Previous studies have mainly focused on the phytochemical composition of W. sinensis leaves (Rokosz et al, 2018), B. hispida fruits (Han et al, 2013;Islam et al, 2021), L. cylindrica seeds (Yoshikawa et al, 1991;Al-Snafi, 2019), and C. pepo fruits (Kulczyński and Gramza-Michałowska, 2019). Phytochemical analysis has revealed that these plants are rich in flavonoids, phenolic acids, tannins, α-tocopherol, and other antioxidants.…”
Section: Introductionmentioning
confidence: 99%